2019
DOI: 10.3390/rs11161872
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Growing Stem Volume of Chinese Fir Plantation Using a Saturation-based Multivariate Method and Quad-polarimetric SAR Images

Abstract: For the planning and sustainable management of forest resources, well-managed plantations are of great significance to mitigate the decrease of forested areas. Monitoring these planted forests is essential for forest resource inventories. In this study, two ALOS PALSAR-2 quad-polarimetric synthetic aperture radar (SAR) images and ground measurements were employed to estimate growing stem volume (GSV) of Chinese fir plantations located in a hilly area of southern China. To investigate the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
(156 reference statements)
0
20
2
Order By: Relevance
“…Thus, the quad-polarimetric SAR images should provide greater potential to obtain higher saturation levels than optical images. However, the GSV saturation values of the Chinese fir plantations obtained by Long et al [10] are much smaller compared with those of the Chinese pine forests in this study. This might be mainly due to the uncertainties that are induced by the complexity of processing SAR images and the lack of the feature variables that accurately capture the characteristics of the data saturation.…”
Section: Effective Methods For Improving Spectral Variable Selection contrasting
confidence: 81%
See 1 more Smart Citation
“…Thus, the quad-polarimetric SAR images should provide greater potential to obtain higher saturation levels than optical images. However, the GSV saturation values of the Chinese fir plantations obtained by Long et al [10] are much smaller compared with those of the Chinese pine forests in this study. This might be mainly due to the uncertainties that are induced by the complexity of processing SAR images and the lack of the feature variables that accurately capture the characteristics of the data saturation.…”
Section: Effective Methods For Improving Spectral Variable Selection contrasting
confidence: 81%
“…This might be mainly because different optical images and spectral variable selection methods were utilized and the data fusion was ignored. Moreover, Long et al [10] obtained the saturation values of GSV ranging from 140.05 m 3 /ha to 349.84 m 3 /ha using a saturation-based multivariate method and quad-polarimetric synthetic aperture radar SAR images for Chinese fir plantations in the Hunan area of south central China. Although the Chinese fir plantations are also biologically similar to the Chinese pine plantations, mature Chinese fir plantations in south central China usually have larger per unit GSV values than the Chinese pine plantations in north China.…”
Section: Effective Methods For Improving Spectral Variable Selection mentioning
confidence: 99%
“…Facing the challenge of spectral saturation, the models and remote sensing images are initially considered to increase the saturation levels [26,27]. Excepting the linear and non-linear models, several complexed machine learning and deep learning algorithms, such as support vector machine model (SVR) [28,29], random forest model (RF) [30], K-nearest neighbor method (KNN) [31], CNN and ensemble learning algorithms, are often employed to map GSV in various forest and the results showed that these models can improve the accuracy of GSV by delaying the saturation.…”
Section: Introductionmentioning
confidence: 99%
“…For the parameters approach, the saturation level was regarded as one of parameters. The semi-exponential model is traditional parameters approach for estimating the saturation levels using polarmetric SAR images, and the saturation level is one parameter of the model directly derived from solving the models [27,46]. Additionally, it has been found that the principle of the kriging model based on the semi-covariance function in geostatistics is similar to the phenomenon of spectral saturation, and a spherical model is also used to quantitatively estimate the saturation values of AGB using spectral reflectance from Landsat imagery, and the results indicated that the saturation levels of AGB highly related to forest types and slope aspects [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The forest growing stock Remote Sens. 2021, 13, 4631 2 of 18 volume (GSV) is a crucial indicator of the quality of planted forests [6][7][8]. Typically, fieldmeasured methods are considered the most accurate way to estimate GSV, but the process is time-consuming and labor-intensive [6,7].…”
Section: Introductionmentioning
confidence: 99%